Editorial: The politics of evidence, data and research in anti-trafficking work - Yea, Sallie (Anti-Trafficking Review, 2017)
Since the mid-2000s, critical commentators have raised concerns about both the paucity of evidence on important aspects of human trafficking, and the difficulty of obtaining meaningful data. Policy formations, advocacy campaigns, concrete interventions, and popular understandings of human trafficking have all had accusations of wild claims and unfounded assumptions levelled at them. Guesstimates prevail and take on a life of their own in such a context. Calls for more robust evidence to prove or disprove claims about the nature, extent and location of human trafficking, the characteristics of trafficked persons, and the continued investment in particular types of responses have abounded. This has occurred in light of the growing potential for unsubstantiated claims to fulfil the place of rigorous evidence to inform anti-trafficking work.